The Analysis of Angin Puting Beliung Risk Rate by Utilization of Remote Sensing and Geographic Information Systems in Semarang - Adil Yusuf Fadillah; Agus Anggoro Sigit; Muhammad Riza Nurdin (International Journal for Disaster and Development Interface, 2021)
This study examines the risk rate of Angin Puting Beliung in Semarang of Central Java. The Angin Puting Beliung is a local designation for small-scale tornadoes that occur in Indonesia, originates from differences in pressure of a weather system, leads to strong winds. Between January 2014 and December 2018, the occurrence of Angin Puting Beliung in Semarang city of Central Java reached 91 times with a total financial loss of around IDR 852,500,000 (USD 60,000). High population densities and settlements without being followed by control of spatial use and land-use change make Semarang more at risk of being hit by a tornado. This study specifically aims to determine the level of physical, social, and economic vulnerability as well as to analyze the risk level of Angin Puting Beliung in Semarang city. The survey is used as the main method in this study. Samples were taken to represent the population namely land cover, slope, and land surface air temperature with data analysis using a weighted tiered quantitative method to answer the purpose of knowing the distribution of hazard and vulnerability areas and analysis of the results of mathematical calculations to determine the risk of Angin Puting Beliung. The results obtained show that Semarang city has a high hazard level of 28,502% which is mostly found in the southwest and northeast of Semarang. High levels of vulnerability are in the sub-districts of West Semarang, Mijen, Gunung Pati, and Tembalang. The risk level with a high class ranks the least, namely from other classes with a distribution in the sub-district of Tugu and Tembalang, accounted at 16.294%.